STUDENTS’ EXPOSITORY WRITING: A CASE STUDY IN PARAGRAPH WRITING CLASS - Puspita Sari (Universitas Widyatama, 2021)
This paper is entitled Students’ Expository Writing: A Case Study in Paragraph Writing Class. It aims at investigating whether the students' expository writing has met the correct writing structure or not. In addition, this study determines what kind of writing patterns are used by students in conveying their writing. The method used in this research is descriptive analysis method. A method used to find the elements and characteristics of a phenomenon, including correctness of structure of expository writing and types of expository writing used by students in conveying their ideas. The data are taken from students’ expository writing with different topics suggested by lecturers at beginning of the lecturing. The results shows that (1) students have fulfilled the structure of expository writing, which consists of an Introductory Paragraph, Body of Paragraph and closed with a conclusion and (2) students use 4 types of paragraphs in conveying their ideas, namely descriptive composition, cause and effect essay, compare and contrast essay and how to do something essay. More specifically, topic 1 (Education) uses the types of compare and contrast essay and descriptive composition, topic 2 (Healthy lifestyle) uses the types of descriptive composition and how to do something essay. Lastly, topic 3 (The Effect of Technology) uses the types of cause and effect essay and the descriptive composition.